Effect of Salicylic Acid on Triterpenoid Biosynthesis and Reactive Oxygen Species Content in Ganoderma applanatum Mycelium - GUO Peijie, WANG Zhanbin, XIA Yongqiao, WANG Xingpei (Shipin Kexue)
This study investigated the effect of different concentrations of salicylic acid (SA) on triterpenoid biosynthesis and reactive oxygen species (ROS) content in Ganoderma applanatum mycelium. The results showed that the maximum content of total triterpenoid of 60.793 mg/g was obtained at an SA concentration of 250 µmol/L. SA at 250 µmol/L was added at different time points during the 10-day culture period. The optimal timing of induction was found to be addition of SA on the 6th day, and the total triterpenoid content reached 67.413 mg/g upon culture completion, which was 59.2% higher than that of the control group. The analysis of antioxidant enzyme activity and malondialdehyde (MDA) levels in the mycelium of G. applanatum indicated that the intracellular catalase (CAT) activity and MDA levels peaked on the 8th day, which increased by 55.3% and 77%, respectively compared with the control group. The activity of total superoxide dismutase (SOD) continuously increased, indicating that SA could induce an increase in reactive oxygen species (ROS) content. Untargeted metabolomic analysis of terpenoid metabolites showed that under optimal induction conditions, 7 out of 22 terpenoid metabolites were up-regulated, one was down-regulated, and 14 remained unchanged. Kyoto Encyclopedia of Genes and Genomes (KEGG) metabolic pathway and heatmap analyses found that the up-regulated metabolite farnesol to be an important precursor in the triterpenoid biosynthesis pathway and its production was significantly correlated with ROS. In conclusion, SA is an effective exogenous inducer of triterpenoid biosynthesis in G. applanatum mycelium. This study provides an effective method for increasing the triterpenoid content in G. applanatum mycelium and offers new insights into the mechanism of SA-induced triterpenoid biosynthesis.